The potential of using sets of specimens to handle species concepts - Baker, Edward (PeerJ PrePrints, 2015)
The use of notation and concepts from mathematical set theory is investigated as a method for describing species concepts, and potentially higher level taxa. These methods may facilitate the easy databasing of species concepts, allowing the concepts themselves to become citable through the provision of unique identifiers. The increase in unique identifiers (such as Life Science Identifiers or Digital Object Identifiers) for biological specimens in recent years may make this approach more feasible than it would have been previously.
Keywords: set noation; taxonomy; biological specimens; species concept